2013
DOI: 10.1016/j.ypmed.2013.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and behavior of physicians regarding predictive genetic tests for breast and colorectal cancer

Abstract: Targeted educational programs are needed to improve the expertise of physicians, and, ultimately, to enhance the appropriate use of genetic tests in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 34 publications
6
60
0
1
Order By: Relevance
“…In this context, doctors have been envisaged as the key players in properly incorporating emerging DNA technologies in the health care system [3, 4], leading to calls for enhanced genomic education for healthcare professionals. Nevertheless, several studies conducted in USA, Europe, and Canada showed unsatisfactory level of clinicians' ability to use genetic tests in clinical care [3–5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, doctors have been envisaged as the key players in properly incorporating emerging DNA technologies in the health care system [3, 4], leading to calls for enhanced genomic education for healthcare professionals. Nevertheless, several studies conducted in USA, Europe, and Canada showed unsatisfactory level of clinicians' ability to use genetic tests in clinical care [3–5]. …”
Section: Introductionmentioning
confidence: 99%
“…However, Marzuillo et al reported a significant lack of knowledge on BRCA1/2 and APC tests among Italian medical doctors [5], irrespective of their specialty. Along similar lines, we conducted survey on Italian doctors attending postgraduate medical schools in order to examine the level of education they had received on genetic tests for breast and colorectal cancer during their recent medical training.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with Italian physicians, who previously showed significant training needs in the field of efficacy, effectiveness and economic evaluation of health interventions [42,43], public health attitudes towards predictive genetic testing appear to be more positive among public health practitioners. For example, the percentage of public health professionals who agree that the selection of predictive genetic testing to be delivered to the population should be based on the principles of efficacy and cost-effectiveness are higher than those found among Italian physicians in another survey [44]. Globally, the public health community in Italy appears to be more prepared than physicians for a responsible and appropriate introduction of DNA-technology into health care and public health practice.…”
Section: Discussionmentioning
confidence: 94%
“…Other reported barriers to clinicians' referral for cancer genetic risk evaluation include the limited knowledge on hereditary cancer and the lack of specific training [23,24]. Indeed, a recent survey indicates that the knowledge of and attitudes about BRCA genetic testing of Italian physicians are heterogeneous [25], suggesting that targeted educational and training programs in this field are needed in our country.…”
Section: Discussionmentioning
confidence: 99%